Error Analysis of Translation: A Case Study of ELT Department Students/Tishk International University - Rawand Sabah Ahmed; Yassen Muhammad Awla (Zanco Journal of Humanity Sciences)
The paper aims to investigate the types of errors committed by students of English Language Teaching department who study translation at the third year of university. Identifying the types of errors in students' translation products is not only significant for the teacher who knows how to address the students' difficulties but also for the students who get an idea of the causes and problems they face in order to tackle them in their translation projects. This also allows the teacher to demonstrate the students' level of mastering the linguistic and translations performances. To conduct this study, nearly 50 students of ELT department who study translation at their third-grade students participated in the study. The data of the research was collected form the students’ weekly assignment of translation from Kurdish to English. Third year students who study translation have weekly assignment of translation.  The data of their assignments were randomly collected by the teacher to identify and classify types of errors they have in their assignment. Later, with the help of four translation teachers, the errors were identified and classified againTeachers of translation checked the students’ translation tasks at different times so as to count for the reliability and validity of the study. For the current study, the classification of error analysis operated by Pospescu (2012) is used. He used the taxonomy of error analysis in terms of three categories: Linguistic errors, comprehension errors, and translation errors, as well as sub classification of each type. Linguistic errors involve errors in morphology, syntax and collocations. Errors of comprehension include misinterpretation of syntax or lexis. The results showed that the translation and linguistic errors are the most common types of errors committed by the students, of which grammatical and lexical errors are the most common committed by the students. The sources of many errors may be attributed to context and pragmatic analysis of translated texts. The paper offers some suggestions and recommendations for further researches and investigations for improving students' translation performance.